Adapt or Exchange: Making changes within or between contexts in a modular plant scenario - Romy Müller; Leon Urbas (Journal of Dynamic Decision Making)
Most psychological studies investigating the balance between stability and flexibility in decision making use specific restrictions in their scenarios. These restrictions are likely to affect decision process, and it is unclear which of the findings can be transferred to more naturalistic decision contexts that call for a balance between stability and flexibility. Therefore, the present study used a scenario that is inspired by the problem structure found in a particular domain: Adapt/Exchange decisions in modular chemical plants. In this setting, we investigated whether participants engage in a thorough comparison of options and whether they perseverate on their previous choices when decision sequences increasingly favour one or the other option. The results suggest that instead of comparing options, participants used a satisficing strategy, checking whether Adapt was good enough and only computing an Exchange solution when it was not. Sequence effects were found, but their direction was opposite to the choice perseveration predicted from the literature: In sequences initially favouring Adapt, participants started exploring the Exchange option early on, while in sequences initially demanding Exchange, they preferred Adapt as soon as it became possible. The results raise questions about the application of psychological theories to complex decisions between qualitatively different options.